Micro-Controller Based Soft Start for three Phase Induction Motor - Ghosh, Maharshi; Kumar, Govind; Kumar Ray, Saurabh; Sharma, Rohit; Pattanayak, Prasanta; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
This project attempts a new speed control technique for the A.C three-phase induction motor. It uses optimized soft-start to start induction motor. At the time of starting Induction motor draws high amount of current (Starting Current) which is 6 times of full load current, to prevent this starter is needed. Here we are using PIC18F4550 to control the soft-start. Input control signal to PIC, which gives Digital output to DAC (Digital to analog converter). DAC converts digital input of PIC to analog output. This analog output is given to Op-Amp, for maintain reference output, which in turn is gives supply to opto-coupler for protection of Control Circuit. It presents a design of a low-cost; high-efficiency drive capable of supplying a three-phase induction motor.